2016
DOI: 10.1037/fam0000155
|View full text |Cite
|
Sign up to set email alerts
|

Relational closeness moderates the association between maternal overcontrol and children’s depressive symptoms.

Abstract: Though numerous studies have examined the relationship between parental overcontrol (OC) and child anxiety, few have examined the association between OC and children's depressive symptoms. However, there are conceptual reasons to believe that overcontrolling parenting may also be relevant to depressive symptomatology, as well as to anticipate that other aspects of the parent-child relationship may moderate the association between the two. In this study we examine the association between self-reported maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…This framework also highlights the centrality of youth's perceptions of attunement. Consistent with this conceptualization, child‐reported (but not mother‐reported) parent–child closeness moderates the association between OC and depressive symptoms in middle childhood (Sichko, Borelli, Rasmussen, & Smiley, ).…”
Section: Oc In Context: Parental Attunementmentioning
confidence: 81%
See 1 more Smart Citation
“…This framework also highlights the centrality of youth's perceptions of attunement. Consistent with this conceptualization, child‐reported (but not mother‐reported) parent–child closeness moderates the association between OC and depressive symptoms in middle childhood (Sichko, Borelli, Rasmussen, & Smiley, ).…”
Section: Oc In Context: Parental Attunementmentioning
confidence: 81%
“…This finding highlights that OC cannot be understood in isolation from its context (Darling & Steinberg, ). Maternal warmth, closeness, and child ethnicity each moderate the effects of OC on preschoolers' externalizing behaviors (Akcinar & Baydar, ), children's depression (Sichko et al., ), and adolescents’ affect (Mason et al., ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depression is associated with negative consequences, including academic difficulties, interpersonal dysfunction, as well as health problems (Berndt et al, 2000; Zlotnick et al, 2000; Korczak and Goldstein, 2009), and it may persist into adulthood if left untreated (Aalto-Setälä et al, 2002). Many prior studies have demonstrated that family context and internal resources are potential factors associated with adolescent depression (Elovainio et al, 2012; Moksnes et al, 2012; Sichko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The PCT is a standardized laboratory task used in prior investigations (see Borelli, Burkhart, Rasmussen, Smiley, & Hellemann, 2018;Borelli et al, 2015;Sichko, Borelli, Rasmussen, & Smiley, 2016;Smiley et al, 2016). It involves computer presentation of six 3-by 3-tile geometric puzzles adapted from the Block Design task in the Wechsler Intelligence Scale for Children-III (Wechsler, 1991).…”
Section: Performance Challenge Taskmentioning
confidence: 99%